PELATIHAN DAN PENGENALAN TEKNOLOGI INFORMASI (TI) DASAR UNTUK ANAK-ANAK DESA AMPELAN BONDOWOSO - Sari, Vega Kartika; Deana Nathania Damayanti; Naura, Lintang Arsa; Furqon, Muhammad (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2024)
Ampelan Village, which is in Wringin District, Bondowoso Regency, has a large number of residents, including elderly residents, adults and children. One of the problems in Ampelan Village is the lack of children's understanding of the world of technology. In fact, understanding it is currently very necessary, especially for children who are currently studying as a preparation for facing future challenges. One of the programs carried out in Ampelan Village is basic IT training for children which aims to equip the younger generation with digital skills so they can keep up with developments that are closely related to digitalization in education. This program is designed to provide a basic understanding of the use of computers, the internet and platforms to support their school work. The activity was attended by 31 children, who were very enthusiastic during the activity. The result of this activity was an increase in participants' understanding of the basics of navigation on laptops, typing, and the use of Microsoft Word and Microsoft PowerPoint. The hope is that this program can help access the introduction of technology education in rural areas to reduce the digital divide.